Role of PI3K, mTOR and Akt2 signalling in hepatic tumorigenesis via the control of PKM2 expression. (18th July 2013) - Nemazanyy, Ivan; Espeillac, Catherine; Pende, Mario; Panasyuk, Ganna
Abstract : To sustain increased growth, rapidly proliferating cells, such as tumour cells, undergo metabolic adaptations. In recent years, the mechanisms of glycolysis activation as a key metabolic adaptation in proliferating cells became the topic of intense research. Although this phenomenon was described more than 50 years ago by Otto Warburg, the molecular mechanisms remained elusive. Only recently, it was demonstrated that the expression of specific glycolytic enzymes, namely PKM2 (pyruvate kinase M2) and HK2 (hexokinase 2), occurs simultaneously with the glycolytic addiction of cancer cells. The PI3K (phosphoinositide 3-kinase)/mTOR [mammalian (or mechanistic) target of rapamycin] signalling pathway is a central signalling hub co-ordinating the growth in response to growth factor signalling and nutrient availability. Not surprisingly, it is found to be activated in the majority of the tumour cells. In the present article, we discuss the requirement of different PI3K/mTOR downstream effectors for the metabolic adaptation in liver cancer cells driven by this signalling pathway. We provide evidence for a selective involvement of the mTOR target Akt2 in tumoral growth. In addition, PTEN (phosphatase and tensin homologue deleted on chromosome 10)-negative human hepatocellular carcinoma cell lines display an up-regulation of PKM2 expression in an Akt2-dependent manner, providing an advantage for cell proliferation and anchorage-independent growth. Our data have implications on the link between the metabolic action of insulin signal transduction and tumorigenesis, identifying Akt2 as a potential therapeutical target in liver malignancies depending on cancer genotype.